Comparative Evaluation of Outcomes and Patient Satisfaction Between Single-Incision and Conventional Multi-Port Laparoscopic Surgeries - Ghulam Murtaza, Ezzah Naseer, Hafeezullah, Saleem Shahzad Gondal, Khalid Ali, Rana Shoaib Aslam, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Single-Incision Laparoscopic Surgery (SILS) has been introduced as a more cosmetically appealing and potentially less painful alternative to Conventional Multi-Port Laparoscopic Surgery (CMP-LS). However, comparative clinical evidence from tertiary care hospitals in Pakistan remains limited. This study evaluates operative efficiency, postoperative recovery, complication rates, cosmetic outcomes, and patient satisfaction among patients undergoing SILS and CMP-LS. Objectives: To compare intraoperative and postoperative outcomes, complication rates, cosmetic satisfaction, and overall patient satisfaction between SILS and CMP-LS performed at two major tertiary care centers. Methods: A prospective comparative observational study was conducted in the General Surgery Departments of Nishtar Hospital Multan and Gulab Devi Hospital Lahore from May 2022 to February 2023. A total of 100 patients undergoing elective laparoscopic appendectomy or cholecystectomy were enrolled and allocated into the SILS group (n=50) or CMP-LS group (n=50). Operative parameters, postoperative pain scores, hospital stay, wound complications, cosmetic satisfaction, and overall patient satisfaction were evaluated. Statistical analysis was performed using SPSS 26 with significance set at p<0.05. Results: SILS demonstrated significantly longer operative time (p=0.001) but showed superior postoperative outcomes, including lower pain at 12 and 24 hours (p=0.01 and <0.001, respectively) and shorter hospital stay (p=0.003). Complication rates were similar between groups (p>0.05). Cosmetic satisfaction was significantly higher in the SILS group (p<0.001), and overall patient satisfaction favored SILS (92% vs. 78%; p=0.04). Conclusion: SILS provides clinically meaningful advantages in postoperative comfort, cosmetic outcomes, and patient satisfaction while maintaining comparable safety to CMP-LS. Despite longer operative time, SILS represents a feasible and patient-centered alternative in tertiary surgical practice. Keywords: Single-incision, Laparoscopy, Multi-port, Patient satisfaction, Cosmetic outcomes, Minimally invasive surgery